BEETLES. - Siti Nurlydia, Sazali; Ratnawati, Hazali; Nurfarida Anum, Zainaddin; Tan, Wei Lim; Chai, Chia Yee; Chow, Jia Yii; Marlina Bianah, Soui; Chum, Yit Seng; Nur Asya Aliah, Mohd Baki; Nur Asha Irdina, Mohd Najib; Ma, Ming Hui; Mohamad Jalani, Mortada (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
Beetles, which belong to the order Coleoptera, are among the most abundant insects and are cosmopolitan as well as ubiquitous. They can be distinguished by their biting mouthparts and chitinous forewings, known as elytra, which serve as protective covers for their hindwings. Being such a successful group, beetles play many ecological roles in tropical ecosystems, including as decomposers, pollinators, seed dispersal agents and natural predators. From an anthropogenic viewpoint, they can be perceived as pests and biological control agents as well as bioindicators.